2018
DOI: 10.1007/s13312-018-1274-8
|View full text |Cite
|
Sign up to set email alerts
|

Predictors and Outcome of Acute Kidney Injury in Children with Diabetic Ketoacidosis

Abstract: Majority of children with AKI and DKA, recover with hydration. Hyperchloremia at 24 hours had independent association with AKI, although cause-effect relation could not be ascertained.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
55
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(59 citation statements)
references
References 14 publications
2
55
0
2
Order By: Relevance
“…Both studies demonstrated that a high proportion of patients hospitalized for DKA developed AKI, which is consistent with our findings. In contrast, the prevalence of AKI in children with DKA was only 35.4% in India [20]; however, the baseline creatinine clearance they used to define AKI was not mentioned in their study. A recent study in Israel showed that the proportion of children with AKI who were admitted for DKA was only 30% [21], which is much lower than our result.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…Both studies demonstrated that a high proportion of patients hospitalized for DKA developed AKI, which is consistent with our findings. In contrast, the prevalence of AKI in children with DKA was only 35.4% in India [20]; however, the baseline creatinine clearance they used to define AKI was not mentioned in their study. A recent study in Israel showed that the proportion of children with AKI who were admitted for DKA was only 30% [21], which is much lower than our result.…”
Section: Discussionmentioning
confidence: 90%
“…The reported prevalence of AKI in patients with DKA has been highly variable across different studies [19][20][21][22]. In the study of Orban et al, which included 94 patients, 50% of adults who were admitted for DKA met the RIFLE criteria for AKI [22].…”
Section: Discussionmentioning
confidence: 99%
“…Another serious consequence of DKA is the development of AKI. Despite the fact that, AKI occurs at a higher rate in hyperglycemic hypoerosmolar state, it's incidence on children with DKA is scarce 18,19 . The recent report from Weissbach et al, demonstrated the AKI incidence at DKA presence as 30% possibly due to prerenal mechanisms 20 .…”
Section: Discussionmentioning
confidence: 99%
“…The chloride elevation in this study was very modest in both groups-only 4 mmol/L for the Plasma-Lyte group and 6 mmol/L for the normal saline group [1]. If we look at the study of Baalaaji et al [2], where all the patients were resuscitated with saline, the chloride in the non-AKI group was 106.6 mmol/L versus 118.6 mmol/L in the AKI group, a difference in chloride of 12 mmol/L [2]. In that study, twenty-eight (35%) children were diagnosed with AKI: twenty (71.4%) recovered with hydration alone while 8 (28.6%) required RRT [2].…”
mentioning
confidence: 57%